2012
DOI: 10.1063/1.4744947
|View full text |Cite
|
Sign up to set email alerts
|

A full free spectral range tuning of p-i-n doped gallium nitride microdisk cavity

Abstract: Effective, permanent tuning of the whispering gallery modes (WGMs) of p-i-n doped GaN microdisk cavity with embedded InGaN quantum dots over one free spectral range is successfully demonstrated by irradiating the microdisks with a ultraviolet laser (380nm) in DI water. For incident laser powers between 150 and 960 nW, the tuning rate varies linearly. Etching of the top surface of the cavity is proposed as the driving force for the observed shift in WGMs, and is supported by experiments. The tuning for GaN/InGa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…However, these techniques complicate the handling of multiple cavities and tend to degrade optical and mechanical properties by surface modification. Ultraviolet light at or above the bandgap was used to photo-etch gallium nitride devices 29 30 31 and trim silicon optical structures 32 , however, with limited precision. Fluidic tuning was achieved by water infiltration and evaporation at the level of individual photonic cavities but with little permanence 33 .…”
mentioning
confidence: 99%
“…However, these techniques complicate the handling of multiple cavities and tend to degrade optical and mechanical properties by surface modification. Ultraviolet light at or above the bandgap was used to photo-etch gallium nitride devices 29 30 31 and trim silicon optical structures 32 , however, with limited precision. Fluidic tuning was achieved by water infiltration and evaporation at the level of individual photonic cavities but with little permanence 33 .…”
mentioning
confidence: 99%
“…[12][13][14][15][16] However, the traditional GaAs and GaN WGM microcavities are of disk structures formed by the etching technique. 20,21 It means that high performance thin film deposition system and etching machine are indispensable for fabricating ZnO microdisk WGM cavities. So it is of significance to explore a simple and economic method to naturally grow disk-shaped ZnO micro/nanostructures for WGM microlasers.…”
mentioning
confidence: 99%
“…As such, the study of effects of defects on III-nitride devices is crucial to their improvement and optimisation. This review will focus on the effects of defects on III-nitride microdisk cavities, an application of III-nitride materials which has garnered considerable attention in the past years [7,[12][13][14][15][16]].…”
Section: Introductionmentioning
confidence: 99%
“…This is absolutely crucial in mitigating the polarization fields inherent to c-plane nitrides which would otherwise result in etching at only one interface of the sacrificial layer[76]. As a result, the InGaN SSL design proposed by Haberer et al with thin alternating layers of varying In content has become a commonly used sacrificial structure for the undercutting of microdisks by PEC etching[7,10,13,15,50,54,59]. However, the relaxation of pseudomorphic InGaN epilayers on GaN substrates is known to result in the generation of dislocations[77], which in the case of the InGaN SSL growth can result in a second source of dislocations, separate to those associated with the GaN pseudosubstrate.. El-Ella et al first demonstrated that the growth of the SSL can result in generation of dislocations by growing a series of structures containing SSLs of varying In content[75].…”
mentioning
confidence: 99%